2016
DOI: 10.1245/s10434-016-5174-7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatectomy for Hepatocellular Carcinoma with Bile Duct Tumor Thrombus, Including Cases with Obstructive Jaundice

Abstract: SynopsisHepatectomy should be considered for hepatocellular carcinoma with bile duct tumor thrombus.3 Abstract Purpose: The purpose of this study was to evaluate the short-and long-term outcomes of hepatectomy for hepatocellular carcinoma (HCC) with bile duct tumor thrombus (BDTT), including cases with obstructive jaundice. Methods:We reviewed 42 HCC patients with BDTT, including 6 patients who needed preoperative biliary drainage due to obstructive jaundice and 732 HCC patients without BDTT. We analyzed the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…Thus far, several studies have explored the component and features about HCC with BDTT [5,8,17]. Many surgeons reached a consensus that hepatectomy for HCC with HBDTT is necessary [10,11,43,44]. In comparison, bile duct resection in patients with HCC and HBDTT remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, several studies have explored the component and features about HCC with BDTT [5,8,17]. Many surgeons reached a consensus that hepatectomy for HCC with HBDTT is necessary [10,11,43,44]. In comparison, bile duct resection in patients with HCC and HBDTT remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that the large lesions, capsule in ltration, poor differentiation, portal vein invasion and intrahepatic metastasis were more frequently observed in HCC patients with BDTT [5,18,19]. These differences suggested patients with BDTT had more particular in ltrative nature, which accounted for poorer prognosis than those without BDTT even after curative resection [7][8][9][18][19][20][21]. Since the bile duct and portal vein are encapsulated in the same Glissonian sheath, tumors can easily involve both of them.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on the background of biliary invasion cases. In an analysis of 774 HCC patients who underwent surgery, Orimo et al [23] reported that 43 patients with bile duct invasion had higher serum AFP levels, larger tumor size, and portal vein invasion. Jang et al [24] reported a pathological study of 363 HCC cases, including 13 cases of bile duct invasion, and described that bile duct invasion was often accompanied by microvascular invasion.…”
Section: Discussionmentioning
confidence: 99%